1992
DOI: 10.1037/0022-006x.60.5.664
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of antidepressant outcome under "blinder" conditions.

Abstract: A meta-analysis of 22 studies of antidepressant outcome assessed the level of medication effects under conditions thought to be less subject to clinician bias than those in the typical double-blind drug trial. Studies were included only if, in addition to a newer antidepressant group, they also contained both standard antidepressant and placebo control groups. Effect sizes were quite modest and approximately one half to one quarter the size of those previously reported under more transparent conditions. Effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
111
5
2

Year Published

1995
1995
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(124 citation statements)
references
References 31 publications
(46 reference statements)
6
111
5
2
Order By: Relevance
“…However, the anxiety effect is not a great deal smaller than the overall mean of 0.5 found by Lipsey and Wilson (1993) in their meta-analysis of meta-analyses of psychological interventions in many settings. Also four meta-analyses of antidepressants for depression have reported effect sizes between 0.19 and 0.79 (Smith et al, 1980;Shapiro and Shapiro, 1982;Quality Assurance Project, 1983;Steinbrueck et al, 1983;Greenberg et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…However, the anxiety effect is not a great deal smaller than the overall mean of 0.5 found by Lipsey and Wilson (1993) in their meta-analysis of meta-analyses of psychological interventions in many settings. Also four meta-analyses of antidepressants for depression have reported effect sizes between 0.19 and 0.79 (Smith et al, 1980;Shapiro and Shapiro, 1982;Quality Assurance Project, 1983;Steinbrueck et al, 1983;Greenberg et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…This amplified placebo effect is difficult to demonstrate empirically, but several metaanalyses have found that trials with more rigorously blind conditions demonstrated lower medication effects, compared with placebo, than other trials. 2,3 These metaanalyses have been criticized with some justification, partly owing to the low quality of the included trials. Nevertheless, although critics are right to point out that the effects of placebo amplification have not been conclusively demonstrated, neither have they been refuted.…”
Section: Short-term Studiesmentioning
confidence: 99%
“…What we talk about is actually alexithymia.Coles et al (15) believes that people suffering from stomatopyrosis have hidden energy as a psychical disturbance, as this is what the test he conducted revealed. Domb and Chole (3) studied the possibility of cancerophobia being a mental etiological factor with respondents suffering from stomatopyrosis and the results he obtained showed a high percentage of the interrelatedness between cancerophobia and stomatopyrosis.Greenberg et al (16,17,18) concluded that psychotherapy and psychopharmacotherapy are very successful in treating BMS which has occurred as a result of a mental disturbance.Botha (19) dealt with people suffering from stomatopyrosis in whose etiology there was a psychogenic factor. He concluded that psychotherapy and psychopharmacotherapy gave excellent results.…”
mentioning
confidence: 99%